Prediction of preeclampsia by HDP gestosis score - Upadhyay, Anupma; Chaurasia, Amrita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Preeclampsia is a complex obstetrical syndrome and an important contributor to maternal and perinatal morbidity and mortality. A large number of predictive tests and scoring systems have been proposed but ni low resource settings a cheap, quick and reliable scoring system is desirable to adequately predict the risk for all women. This study aimed to study the role of HDP gestosis score in prediction of preeclampsia. Methods: The study was done on 400 antenatal women attending Obstetrics and Gynecology outpatient department of SRN hospital, MLNMC Prayagraj. All enrolled participants were assigned a gestosis score calculated by the ANDROID AP at first visit (<18 weeks of gestation). All women were divided in three groups according to gestosis score of 1, 2 and 3 or more. The participants were then followed throughout pregnancy and development of preeclampsia was noted. Results: Preeclampsia developed in 13.7% of women. THE sensitivity, specificity, positive predictive value, negative predictive value and predictive accuracy of HDP gestosis score were 72.2%, 94.6%, 68.4%, 95.5% and 91.6% respectively. Conclusions: The HDP gestosis score is a simple, cheap, mobile app. Based scoring system which allows provider to quickly assess individual woman risk-for future development of preeclampsia in busy OPD setting. HDP gestosis score is an effective tool to predict at risk women and initiate pharmacological intervention or intensive maternofetal surveillance.